A vibration analysis strategy for quantitative fracture healing assessment of an internally fixated femur with mass-loading effect of soft tissue. (November 2021) - Vien, Benjamin Steven; Chiu, Wing Kong; Russ, Matthias; Fitzgerald, Mark
Vibration analysis methods have been studied to evaluate bone stiffness as a quantifiable mechanical parameter that associates with the degree of fracture healing. However, the effects of soft tissue on the bone frequency response still remain as significant challenges in successfully implementing vibration analysis-based methods as an effective clinical assessment tool. This study presents a computational investigation on the mass-loading effect of soft tissue on a fractured femur bone fixated with an intramedullary nail. An oblique fracture is modelled by a 3 mm osteotomised region, where its elastic modulus is varied from 0% to 100% of the pristine bone elastic modulus to simulate the stages of fracture bone healing. The findings indicate that the first-order torsional and second-order bending modal frequencies change significantly as the fracture region regains stiffness and the significant increase in third-order bending mode amplitude suggests the fracture stiffness has recovered over 1% of the pristine bone stiffness. Furthermore, mass-loading soft tissue does not affect the torsional mode and has negligible effects on the second-order bending modes. An additional inertia strategy is employed to determine a bone healing parameter relating to the femur stiffness by utilising the torsional modal frequency. A normalised torsional flexibility scoring procedure is then devised to evaluate the healing stages of an internally fixated femur. The subsequent results serve as an important pre-requisite to develop a quantifiable bone union measure and for future efficacy testing.